2008
DOI: 10.1634/stemcells.2008-0397
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mass Spectrometry Identifies Drug Targets in Cancer Stem Cell-Containing Side Population

Abstract: A multifaceted approach is presented as a general strategy to identify new drug targets in a breast cancer stem cellcontaining side population. The approach we have utilized combines side population cell sorting and stable isotope labeling by amino acids in cell culture with mass spectrometry to compare and identify proteins with differential expression profiles between side population cells, know to be enriched in cancer stem cells, and nonside population cells, which are depleted in cancer stem cells, for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 61 publications
(76 reference statements)
4
33
0
1
Order By: Relevance
“…Our study indicates that ovarian cancer cells are heterogeneous. SP cells are highly proliferative compared with non-SP cells; SP xenogeneic transplant mice grew more tumours than non-SP xenogeneic transplant mice, as shown from other studies (Chiba et al, 2008;Harris et al, 2008;Steiniger et al, 2008). SP cells have characteristics of cancer stem-like cells.…”
Section: Discussionmentioning
confidence: 59%
“…Our study indicates that ovarian cancer cells are heterogeneous. SP cells are highly proliferative compared with non-SP cells; SP xenogeneic transplant mice grew more tumours than non-SP xenogeneic transplant mice, as shown from other studies (Chiba et al, 2008;Harris et al, 2008;Steiniger et al, 2008). SP cells have characteristics of cancer stem-like cells.…”
Section: Discussionmentioning
confidence: 59%
“…Many studies demonstrated that selection of chemotherapyresistant cells by using anticancer drugs would be an effective means to enrich the CSC-like subpopulation, 28,29 and CSCs indeed possessed intrinsic properties that mediated their resistance to chemotherapy. 30,31 Lzumiya et al found that 5-FU-pretreated pancreatic cancer cells expressed enhanced levels of the stemness genes OCT4 and NANOG, 32 and exhibited a so-called CSC-like phenotype, including a sphere-forming capability.…”
Section: Discussionmentioning
confidence: 99%
“…The breast cancer SP cells in vivo have been shown to be more tumourigenic than NSP cells when tumor cell cultures in immunodeficient mice (Patrawala et al, 2005;Steiniger et al, 2008;Yin et al, 2008). In Zhou et al (2008) study, the sphere cells cultured from SP cells of breast cancer cell MCF7 were enriched in CSC surface markers CD44+CD24-and had higher tumorigenicity.…”
Section: Discussionmentioning
confidence: 98%
“…It implied the sphere cells enrich breast cancer stem/ progenitor cells and preferentially inhibited by NF-κβ pathway inhibitors compared to their non-stem cell counterparts. Studies have demonstrated that MCF7 SP in the mammary gland are more clinically relevant doses of radiation resistant (Woodward et al, 2007) and clinical resistance to chemotherapy (Steiniger et al, 2008;Yin et al, 2008) than the NSP cell population. These properties would suggest that SP cells may also play a key role in breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%